PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN IPS UNTUK MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS DI MADRASAH IBTIDAIYAH - Fatimah Zahra; Titi Nofita; Oman Farhurohman (Jurnal Pendidikan Nusantara, 2025)
This study aims to explore the implementation of the scientific method in Social Studies (IPS) learning at Madrasah Ibtidaiyah (Islamic Elementary Schools) to enhance students’ critical thinking abilities. Social Studies plays a crucial role in deepening students’ understanding of social, cultural, economic, and environmental aspects while fostering empathy and a sense of responsibility. However, the continued use of traditional, teacher-centered methods has limited the optimal development of students’ critical thinking skills.Through a literature review of five scholarly articles, this study reveals that the application of the scientific approach comprising the stages of observing, questioning, reasoning, experimenting, and communicating positively influences students’ active participation, conceptual understanding, and analytical thinking abilities. Nevertheless, questioning and verbal communication skills still require improvement through sustained teacher guidance. Overall, the scientific method has proven effective in creating dynamic and contextual Social Studies learning that emphasizes the development of students’ critical thinking and higher-order thinking skills essential for the 21st century.